Development of monoclonal antibodies against P. gingivalis Mfa1 and their protective capacity in an experimental periodontitis model - Mingya Cao; Siyu Wang; Shengke Zhou; Min Yan; Yu Zou; Yuan Cui; Xinyu Lou; Yichang Gao; Ying Chen; Zijing Han; Yi Qian; Jingying Chen; et al. (mSphere)
ABSTRACT Porphyromonas gingivalis (P. gingivalis), a gram-negative, black-pigmented anaerobe, is a major etiological agent and a leading cause of periodontitis. Fimbriae protein Mfa1 is a key virulence factor of P. gingivalis and plays a crucial role in bacterial adhesion, colonization, biofilm formation, and persistent inflammation, making it a promising therapeutic target. However, the role of anti-Mfa1 antibodies and the underlying protective mechanisms remain largely unexplored. Here, we developed and characterized the monoclonal antibodies (mAbs) targeting the Mfa1 protein of P. gingivalis. Function analysis showed that anti-Mfa1 mAbs mediated bacterial agglutination and inhibited P. gingivalis adhesion to saliva-coated hydroxyapatite and host cells. Notably, anti-Mfa1 mAbs significantly reduced bacterial burden and alveolar bone loss in a P. gingivalis-induced experimental periodontitis model. These results show that anti-Mfa1 mAbs can be beneficial in alleviating P. gingivalis infections, and provide important insights for the development of adequate adjuvant treatment regimens for Mfa1-targeted therapeutics.IMPORTANCEFimbriae (pili) play an important role in bacterial adhesion, invasion of host cells and tissues, and formation of biofilms. Studies have shown that two types of fimbriae of Porphyromonas gingivalis, FimA and Mfa1, are important for colonization and infection through their binding to host tissues and other bacteria. While anti-FimA antibodies have been shown to improve periodontitis, the effect of anti-Mfa1 antibodies on P. gingivalis infection and periodontitis was previously unknown. In this study, we report for the first time that anti-Mfa1 monoclonal antibodies can reduce P. gingivalis infection and improve periodontitis. These findings suggest that Mfa1 represents a promising therapeutic target, and the development of anti-Mfa1 mAbs holds a potential as essential diagnostic and adjunctive therapeutic tools for managing P. gingivalis-related diseases.